2018
DOI: 10.1016/j.sbi.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for eukaryotic mRNA modification

Abstract: All messenger RNAs in eukaryotes are modified co-transcriptionally and post-transcriptionally. They are all capped at the 5'-end and polyadenylated at the 3'-end. However, many mRNAs are also found to be chemically modified internally for regulation of mRNA processing, translation, stability, and to recode the message. This review will briefly summarize the structural basis for formation of the two most common modifications found at internal sites in mRNAs; methylation and deamination. The structures of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…In the human genome, there are tens of thousands of genes encoding proteins and functional RNAs (Pertea et al, 2018). For many of these genes, there are numerous transcript variants that can be generated via different transcription start sites, alternative splicing, and RNA modifications (Fisher and Beal, 2018;Grosjean, 2005;Pertea et al, 2018). In each different cell type, a unique combination of these RNA variants are expressed, ultimately producing the protein and RNA regulators that define the ll given state of the cell.…”
Section: Direct Interactions With the Cell State And Other Devicesmentioning
confidence: 99%
“…In the human genome, there are tens of thousands of genes encoding proteins and functional RNAs (Pertea et al, 2018). For many of these genes, there are numerous transcript variants that can be generated via different transcription start sites, alternative splicing, and RNA modifications (Fisher and Beal, 2018;Grosjean, 2005;Pertea et al, 2018). In each different cell type, a unique combination of these RNA variants are expressed, ultimately producing the protein and RNA regulators that define the ll given state of the cell.…”
Section: Direct Interactions With the Cell State And Other Devicesmentioning
confidence: 99%
“…11 The technical breakthroughs led to the discovery of a series of modications in eukaryotic mRNA, including N 6methyladenosine (m 6 A), N1-methyladenosine (m 1 A), N 6 ,2 0 -Odimethyladenosine (m 6 Am), 5-methylcytidine (m 5 C), N3-methylcytidine (m 3 C), N7-methylguanosine (m 7 G), 2 0 -O-methylation, inosine (I), and pseudouridine (J). [11][12][13] Very recently, N 4 -acetylcytidine was newly discovered to be present in mRNA of mammals. 14 These studies demonstrated that the modications play versatile roles in mRNA processing and eventually affect the epitranscriptomic state of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Inosine (I) is the deamination product of adenosine (A) ( Fig 1) and its formation is catalyzed by deaminases that act on RNA (ADARs) [1,2]. Furthermore, IMP is the first nucleotide that is generated in the de novo purine synthesis pathway and is then enzymatically derivatized to yield the corresponding AMP or GMP (via XMP) [3].…”
Section: Introductionmentioning
confidence: 99%